2009
DOI: 10.1016/j.anbehav.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of queen phenotype, investment and maternity apportionment on the outcome of fights in cooperative foundations of the ant Lasius niger

Abstract: Keywords: aggression black garden ant colony founding competition Lasius niger microsatellite pleometrosis reproductive conflict Cooperative colony founding (pleometrosis) in social insects is an ideal model for investigating how cooperation and competition shape social behaviour among unrelated individuals. In many ant species, foundress associations are more competitive and the colonies survive better compared with singlequeen colonies. However, cooperation among queens breaks down at the time of emergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 63 publications
1
34
1
Order By: Relevance
“…In eusocial insects, for example, fitness could be measured as the production of new queens and males, but a more accurate measure of fitness would consider the number of new colonies initiated by those new queens (Wilson, 1985). However, the success rate of new queens founding colonies can be low (Aron et al, 2009;Pull et al, 2013), and dependent upon many variables (e.g., climate conditions, predator/parasite density, availability of nesting sites, etc.,) (Voss and Blum, 1987;Tschinkel, 1993;Bernasconi and Keller, 1999). Still, group-level fitness can be measured in multiple ways.…”
Section: Fitness Effectsmentioning
confidence: 99%
“…In eusocial insects, for example, fitness could be measured as the production of new queens and males, but a more accurate measure of fitness would consider the number of new colonies initiated by those new queens (Wilson, 1985). However, the success rate of new queens founding colonies can be low (Aron et al, 2009;Pull et al, 2013), and dependent upon many variables (e.g., climate conditions, predator/parasite density, availability of nesting sites, etc.,) (Voss and Blum, 1987;Tschinkel, 1993;Bernasconi and Keller, 1999). Still, group-level fitness can be measured in multiple ways.…”
Section: Fitness Effectsmentioning
confidence: 99%
“…Upon the emergence of the first workers, queens in most pleometrotic associations engage in fatal fights and all but one queen perishes. In Lasius niger, aggression between reproductives is believed to be decisive for determining which queen survives, and the involvement of workers in fights may only have a marginal influence on the outcome of queen selection (Sommer and Hölldobler, 1995;Aron et al, 2009). Across species, earlier work showed that several factors including queen initial mass, mass loss during foundation, body size, productivity and proximity to the brood influence survival (Aron et al, 2009;Balas and Adams, 1996;Keller, 1996, 1998;Sommer and Hölldobler, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In Lasius niger, aggression between reproductives is believed to be decisive for determining which queen survives, and the involvement of workers in fights may only have a marginal influence on the outcome of queen selection (Sommer and Hölldobler, 1995;Aron et al, 2009). Across species, earlier work showed that several factors including queen initial mass, mass loss during foundation, body size, productivity and proximity to the brood influence survival (Aron et al, 2009;Balas and Adams, 1996;Keller, 1996, 1998;Sommer and Hölldobler, 1995). Although these studies provided insights into the mechanisms driving the loss of cooperation in pleometrotic associations, they did not inform on the behavioural rules and information used by queens to start fighting.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to discover the factors that determine which queen survives, with emphasis on testing whether workers assist their mother (e.g. Sommer & Hö lldobler 1995;Bernasconi & Keller 1996;Adams & Balas 1999;Aron et al 2009), although to date such nepotism has not been clearly identified. If workers are incapable of recognizing their mother, they are predicted to favour the most productive queen because she is statistically the most likely to be their mother (Balas 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Queen ants may lose 20 to 40 per cent of their body weight rearing the first workers (Cahan 2001;Aron et al 2009), so there are likely to be trade-offs between early reproduction and the ability to fight or resist worker aggression. Cofounding queens that anticipate queen elimination may therefore invest less in reproduction than singly founding conspecifics, a prediction that has found empirical support (Bernasconi & Strassmann 1999;Cahan 2001).…”
Section: Introductionmentioning
confidence: 99%